Southeast Asian teacher education program (SEA-TEP) professional development: Malaysia - Ramli, Norazsida; Embong, Zulmaryan; Ahmad Noorden, Ahmad Fakhrurrazi (Persatuan STEM Kebangsaan (National STEM Association), 2025)
This Malaysia Country Report highlights the local adaptation and implementation of SEA TEP to address four key challenges in our teacher education landscape: limited exposure to effective instructional practices in STEM, insufficient preparation among novice and in service teachers, a lack of access to high quality learning materials, and gaps in practical experience for pre service educators. These concerns are neither new nor unique to Malaysia, but they require local solutions rooted in collaboration, contextual understanding, and continuous support.